Public Consultations - Orams Casinelli, Peter (2001)
In 1993 when Minera Yanacocha SLR started its mining activities in Peru, it also simultaneously started the practice of public consultations, in order to share information with the different institutions, groups and interested people, in order to generate flows of dialogue and communication permanent. Minera Yanacocha implemented high-level environmental policies and procedures to ensure proper management and conservation of the physical, cultural, and socio-economic environment that surrounds the area of ​​operations. For this reason, it actively adopted Newmont's corporate philosophy and policies, taking the initiative to prepare and present the first Environmental Impact Study in Peru. This document was presented to the Ministry of Energy and Mines and to the Cajamarca community in a disclosure process. This modality has been followed with the Environmental Impact Studies (EIA) related to the expansion of projects in operation and / or the development of new mining operations.